Friend Affiliations and School Adjustment Among Mexican-American Adolescents: The Moderating Role of Peer and Parent Support - Espinoza, Guadalupe (2013)
Studies examining friendships among Mexican-American adolescents have largely focused on their potentially negative influence. The current study examined the extent to which deviant and achievement-oriented friend affiliations are associated with Mexican-American adolescents’ school adjustment and also tested whether support from friends and parents moderates these associations. High school students (N = 412; 49 % male) completed questionnaires and daily diaries; primary caregivers also completed a questionnaire. Although results revealed few direct associations between friend affiliations and school adjustment, several moderations emerged. In general, the influence of friends’ affiliation was strongest when support from friends was high and parental support was low. The findings suggest that only examining links between friend affiliations and school outcomes does not fully capture how friends promote or hinder school adjustment.